2006
DOI: 10.1021/ef060196+
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Asphaltene Adsorption with Model Heavy Molecules over Macroporous Solid Surfaces

Abstract: The adsorption behavior of Athabasca bitumen C 7 asphaltene (AB-C 7 -A) over a macroporous silica-alumina, kaolin, at room temperature is described by comparison with three model molecules such as Xylenol Orange (amine modified, XYO), Violanthrone-78 (VO-78), and Violanthrone-79 (VO-79). The results show that adsorption uptake at equilibrium of these model molecules is independent up to a certain initial concentration limit on the structure, the nature, and the total content of heteroatoms present. The final u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
82
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 34 publications
9
82
0
Order By: Relevance
“…At the equilibrium, the mass adsorbed quantity increases with the fraction size while the mole adsorbed quantity remains constant at 1.073 Â 10 À 4 mol/g (assumption concerning the saturation concentration (q max ) given constant for all fractions). This hypothesis assumes that the asphaltene adsorption is independent of their molecular size as found by Gonzalez et al (2007). Tendencies of the different fractions adsorption are similar except for the third fraction.…”
Section: Estimation Results For Various Asphaltene Fractions Having Dmentioning
confidence: 90%
See 3 more Smart Citations
“…At the equilibrium, the mass adsorbed quantity increases with the fraction size while the mole adsorbed quantity remains constant at 1.073 Â 10 À 4 mol/g (assumption concerning the saturation concentration (q max ) given constant for all fractions). This hypothesis assumes that the asphaltene adsorption is independent of their molecular size as found by Gonzalez et al (2007). Tendencies of the different fractions adsorption are similar except for the third fraction.…”
Section: Estimation Results For Various Asphaltene Fractions Having Dmentioning
confidence: 90%
“…The adsorbed quantity at the equilibrium is equal to 420 mg/g. Several authors have investigated the adsorption of asphaltenes on minerals (Gonzalez andMoreira, 1994, 1991;Gonzalez et al, 2007;Hannisdal et al, 2006). These studies have been performed on various materials with an asphaltenes adsorption range from 1 to 5 mg/m 2 .…”
Section: Parameter Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…Though SiO 2 is often used as a background particle for its lack of toxicity to bacteria [1], the investigation of Adams et al [2] suggested that nano-SiO 2 could inhibit bacterial growth. As a kind of naturally abundant mineral, kaolinite has been widely studied as adsorbent for removal of metal ions and organic pollutants from water [3][4][5][6]. To our knowledge, little investigation has been made on the sorption of organic pollutant by nano-SiO 2 and kaolinite coated with HA.…”
Section: Introductionmentioning
confidence: 99%